2021
DOI: 10.1681/asn.2020071029
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Inhibits Proximal Tubule NHE3 Activity, Preserves GFR, and Restores Euvolemia in Nondiabetic Rats with Induced Heart Failure

Abstract: BackgroundSGLT2 inhibitors reduce the risk of heart failure (HF) mortality and morbidity, regardless of the presence or absence of diabetes, but the mechanisms underlying this benefit remain unclear. Experiments with nondiabetic HF rats tested the hypothesis that the SGLT2 inhibitor empagliflozin (EMPA) inhibits proximal tubule (PT) NHE3 activity and improves renal salt and water handling.MethodsMale Wistar rats were subjected to myocardial infarction or sham operation. After 4 weeks, rats that developed HF an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…This difference may be related to increased Ang II in Akita Hnrnpf RT KO mice since Ang II has been shown to stimulate NHE3 expression [41]. Moreover, studies have demonstrated a discrepancy between NHE3 mRNA expression, protein expression and transporter activity, and post-transcriptional NHE3 phosphorylation is also an important factor [36,42]. Therefore, it is still unclear if changes in NHE3 activity contributes to TGF and natriuresis in Akita Hnrnpf RT KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be related to increased Ang II in Akita Hnrnpf RT KO mice since Ang II has been shown to stimulate NHE3 expression [41]. Moreover, studies have demonstrated a discrepancy between NHE3 mRNA expression, protein expression and transporter activity, and post-transcriptional NHE3 phosphorylation is also an important factor [36,42]. Therefore, it is still unclear if changes in NHE3 activity contributes to TGF and natriuresis in Akita Hnrnpf RT KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…4d) were higher in Akita mice than in Ctrl mice and were markedly lower in Akita Hnrnpf RT KO mice as compared with Akita mice. Recent studies have suggested that the reduction of Na + /H + exchanger isoform 3 (NHE3) activity is the determinant of natriuretic effect of SGLT2i [34][35][36]. Therefore, we also evaluated the Nhe3 (also known as Slc9a3) expression in Akita Hnrnpf RT KO mice.…”
Section: Expression Of Agt and Sglt2 In Akitamentioning
confidence: 99%
“…In a rat model of myocardial infarction (MI)-induced heart failure empagliflozin (start of administration 4 weeks after MI and continued for further 4 weeks) slightly improved contractile function and prevented renal insufficiency. Apart from normalization of increased SGLT2 expression these effects were primarily ascribed to inhibition of renal NHE3 [123]. Unfortunately, it remains unclear if the amelioration of cardiac dysfunction in this study of cardiorenal syndrome is due to improved renal function or due to direct cardiac effects [123].…”
Section: Sglt2i and Contractile Functionmentioning
confidence: 76%
“…Apart from normalization of increased SGLT2 expression these effects were primarily ascribed to inhibition of renal NHE3 [123]. Unfortunately, it remains unclear if the amelioration of cardiac dysfunction in this study of cardiorenal syndrome is due to improved renal function or due to direct cardiac effects [123]. Interestingly, in a non-diabetic mouse model of TACinduced heart failure, empagliflozin treatment prevented worsening of LVEF assessed by echocardiography in vivo as well as ex vivo by an isolated perfused working heart system (excluding a role of extrinsic factors such as hemodynamics or nephroprotection) [124].…”
Section: Sglt2i and Contractile Functionmentioning
confidence: 99%
“…Recent preclinical and clinical research has shown that SGLT2-i treatment provides cardiovascular benefits [6][7][8][9]. The early benefits of treatment with an SGLT2-i to prevent clinical deterioration in the EMPEROR-Preserved trial [1] may indicate the possibility of a natriuretic effect, as an acute increase in urinary sodium excretion was caused by the SGLT2-i empagliflozin in a nondiabetic rat model with induced heart failure [10]. Similarly, reports of beneficial action mechanisms in basic research and favorable clinical results for heart failure in ARNI therapy have increased in recent years [11][12][13].…”
mentioning
confidence: 99%